PELATIHAN DIGITAL MARKETING PADA UMKM TERDAMPAK PANDEMI COVID-19 DI KABUPATEN DEMAK - Arrezqi, Misbakhul; Indrasari, Febrina; Sai’in, Ali; Nurhayati, Ida (Universitas Muhammadiyah Ponorogo, 2022)
The Covid-19 pandemic has caused an economic downturn, an increase in the number of unemployed, a decrease in the number of jobs, and a decrease in people's purchasing power. In these circumstances, online business is a solution to survive and improve the economy. Micro, Small, and Medium Enterprises (MSMEs) were also affected by the decline in sales due to changes in consumer behavior switching to online-based purchases. MSMEs must quickly adapt to changes in consumer behavior to survive amid the economic downturn. Digital marketing training is a solution to help MSMEs adapt to changes in consumer behavior to seek business opportunities and entrepreneurship through digital media. In line with the vision and mission of the Demak Regency Cooperatives and UMKM Trade Office, one of which is to strengthen the community's economy through UMKM, the team is trying to help make it happen in community service activities in digital marketing training. The purpose of this activity is to provide digital marketing training, help participants do marketing through digital media, and carry out digital-based entrepreneurship activities. The method used in this community service activity is in the form of participants attending lectures, discussions, questions, and answers about digital marketing given by practitioners who are experts in their fields then participants follow digital marketing practices. Evaluation of activities is carried out, both before, during, and after the activity is carried out. The results of this activity made 30 MSMEs in Demak Regency able to practice marketing through digital media in their businesses and obtain training modules that can be used as daily practice guides.